2017
DOI: 10.1177/1010428317694314
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel resistance development is associated with biphasic changes in reactive oxygen species, mitochondrial membrane potential and autophagy with elevated energy production capacity in lung cancer cells: A chronological study

Abstract: Paclitaxel (Tx) is one of the first-line chemotherapeutic drugs used against lung cancer, but acquired resistance to this drug is a major challenge against successful chemotherapy. In this work, we have focused on the chronological changes of various cellular parameters and associated effect on Tx (10 nM) resistance development in A549 cell line. It was observed, at initial stage, the cell death percentage due to drug treatment had increased up to 20 days, and thereafter, it started declining and became comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…Currently, Taxol is widely used in the treatment of NSCLC in the clinics. However, many patients have acquired resistance to Taxol, and even those who initially respond will eventually exhibit MDR . We have confirmed that BZML has potent anti‐cancer activity against Taxol‐sensitive or Taxol‐resistant A549 cells through different death modes in vitro .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Currently, Taxol is widely used in the treatment of NSCLC in the clinics. However, many patients have acquired resistance to Taxol, and even those who initially respond will eventually exhibit MDR . We have confirmed that BZML has potent anti‐cancer activity against Taxol‐sensitive or Taxol‐resistant A549 cells through different death modes in vitro .…”
Section: Discussionsupporting
confidence: 54%
“…However, many patients have acquired resistance to Taxol, and even those who initially respond will eventually exhibit MDR. [44][45][46][47] We have confirmed that BZML has potent anti-cancer activity against Taxol-sensitive or Taxol-resistant A549 cells through different death modes in vitro. 10 This paper aimed to evaluate the anticancer activity of BZML in vivo and the mechanism underlying the apoptosis resistance in BZML-treated A549/Taxol cells.…”
Section: Discussionsupporting
confidence: 52%
“…Inhibition of mitochondrial complex I abolished the ability of the resistant cells to invade [ 8 ], suggesting the pivotal role of mitochondria in metastasis of resistant cells. Another recent study showed that mitochondrial oxygen consumption is a vital source of energy in paclitaxel-resistant lung adenocarcinoma cells [ 94 ]. In lung adenocarcinoma cell line A549, mitochondrial membrane depolarization increased during the initial phase where cells died in response to paclitaxel.…”
Section: Mitochondria and Oxphos Play A Pivotal Role In Drug Resistanmentioning
confidence: 99%
“…However, as the cells gained resistance, normal mitochondrial membrane are restored by increased activity of catalase and glutathione peroxidase which counteracted the effect of increased ROS produced as result of paclitaxel treatment. Further, paclitaxel-resistant cells exhibited elevated extracellular acidification rates and oxygen consumption [ 94 ]. Several studies have shown that many cancer cells which are resistant, rely on mitochondrial oxidative phosphorylation for energy [ 96 98 ].…”
Section: Mitochondria and Oxphos Play A Pivotal Role In Drug Resistanmentioning
confidence: 99%
See 1 more Smart Citation